2016
DOI: 10.1186/s12904-016-0147-y
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of interventions for respiratory secretion management in adult palliative care patients—a systematic review

Abstract: BackgroundRespiratory secretions impact negatively on palliative patients. Unfortunately, a gold standard therapy is not yet available. The purpose of this study was to identify which interventions are in use to control respiratory secretions in patients with chronic disease with a poor prognosis and verify their effects on outcomes relevant for palliative care patients.MethodsA systematic review of the literature with narrative summary was conducted. We searched eight electronic databases in April 6th, 2016. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 46 publications
0
20
0
1
Order By: Relevance
“…Cough augmentation techniques, such as lung volume recruitment or manually and mechanically assisted cough, are used to prevent and manage respiratory complications associated with chronic conditions, in particular, neuromuscular disease, 17 patients with tracheal devices, 15 and patients who receive palliative care, 4 and possibly may improve the short-and long-term outcomes for patients with acute respiratory failure. 10,[22][23][24] Nevertheless, a Canadian survey reported that there is a moderate adoption of cough augmentation techniques, and a lack of expertise and knowledge are the potentially modifiable barriers addressed with educational interventions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cough augmentation techniques, such as lung volume recruitment or manually and mechanically assisted cough, are used to prevent and manage respiratory complications associated with chronic conditions, in particular, neuromuscular disease, 17 patients with tracheal devices, 15 and patients who receive palliative care, 4 and possibly may improve the short-and long-term outcomes for patients with acute respiratory failure. 10,[22][23][24] Nevertheless, a Canadian survey reported that there is a moderate adoption of cough augmentation techniques, and a lack of expertise and knowledge are the potentially modifiable barriers addressed with educational interventions.…”
Section: Discussionmentioning
confidence: 99%
“…2 Therefore, the standard care of ICU patients on mechanical ventilation includes respiratory physiotherapy combined with direct suction through the endotracheal tube, which aims to prevent the complications associated with mucus retention, such as pulmonary atelectasis, bronchospasm, tracheobronchitis, and pneu-monia. [3][4][5][6] However, endotracheal tube suctioning is effective in clearing only a small portion of the proximal airway, and this procedure may be insufficient to fully prevent the complications associated with the airway mucus retention. 7…”
Section: Introductionmentioning
confidence: 99%
“…The mainstay of pharmacologic management of secretions is anti-muscarinic drugs such as glycopyrrolate (0.4 mg sc/iv every four hours, as needed), and/or octreotide (300 lg sc q8h, as needed). 67…”
Section: Secretionsmentioning
confidence: 99%
“…No obstante, hasta el momento no existen estudios que demuestren que tenga la misma eficacia en pacientes con enfermedades respiratorias. 18,19 Mucocinéticos Comúnmente referidos como fármacos que mejoran el aclaramiento de la tos al actuar de forma directa en el latido ciliar. Es importante mencionar que no se ha demostrado un efecto consistente sobre el aclaramiento mucociliar en pacientes con historia de enfermedad pulmonar crónica.…”
Section: Mucolíticosunclassified